Tools for ensuring gender equality in the academic sphere of the Republic of Belarus - Kandrichina, Irina N.; Veremeychik, Olga V. (Journal of the Belarusian State University. International Relations, 2020)
The article deals with the problem of ensuring gender equality in the academic sphere of the Republic of Belarus. Despite the absence of normative legal documents in Belarus specifically aimed at ensuring gender equality, there are three key tools that are aimed at establishing gender equality in the country’s higher education institutions: gender education, gender audit, and gender plan. The article analyzes the results of the development and implementation of these tools in the framework of academic cooperation of the Raul Wallenberg Institute of Human Rights and Humanitarian Law (Sweden) and Belarusian universities. The purpose of this article is to systematize the experience of implementing gender plans and gender audits in life activities of higher education institutions, analyze the quality of development, adaptation and implementation of gender equality tools in Belarus. Implementation of the research goal was achieved through the integrated use of methods of system and comparative analysis, systematization and formalization, historical and statistical methods. Based on the analysis, a number of proposals were developed to improve the use of gender equality tools in Belarusian universities: implementation of the principles of active participation and transparency, introduction of relevant gender indicators in the regular reporting system, integration of the theory of chance and the theory of change.